Revision of Hista Oiticica (Lepidoptera: Castniidae) and discussion on the validity of its subspecies - Moraes, Simeão S.; Duarte, Marcelo; González, Jorge M. (Zootaxa, 2010)
Diurnal Lepidoptera tend to have colorful and conspicuous wing patterns, which is the reason the first classifications of day-flying moths and butterflies were based mainly on wing color and pattern characters. This is the case with the Neotropical Castniidae, which are usually large and colorful day-flying moths. One classification listed 134 species in 32 genera while an alternate classification recognized 81 species. In this paper we examine the taxonomic structure of the genus Hista Oiticica. It is the purpose of this paper to evaluate taxonomically useful characters besides wing pattern with the goal of classifying the taxa of Hista rather than classifying the variation of its wing pattern. In so doing, the results resolve the differences between the two proposed classifications of Hista. In addition, a lectotype is designated for Castnia boisduvalii Walker, 1854 (new synonym of Castnia fabricii Swainson, 1823) to ensure the stability of the name. Other new synonyms are proposed for C. fabricii (C. papagaya Westwood, 1877) and Castnia hegemon Kollar, 1839 (C. menetriesi Boisduval, [1875] and C. hegemon variegata Rothschild, 1919).